The diversity of peritoneal dialysis care trajectories: A study based on the REIN registry and SNDS database - Bruno Legendre; Thierry Lobbedez; Cécile Couchoud; Antoine Lanot; Anne Kolko; Cécile Courivaud; Annabel Boyer; Clémence Béchade (PLoS ONE, 2025)
Introduction The integrated care model considers sequences of kidney replacement therapies rather than individual modalities. Data from conventional registries describing trajectories are partial. The aim was to provide a complete description of the peritoneal dialysis pathway. Methods Patients undergoing peritoneal dialysis in France between January 1, 2009, and December 31, 2019, were included. Data from the national REIN (Renal Epidemiology and Information Network) registry and the SNDS (Administrative Database of Outpatient and Inpatient Care Consumption) database were used. Patient trajectories and status (peritoneal dialysis, hemodialysis, mixed and hybrid dialysis, kidney transplantation, and death) were reconstructed. Each dialysis session, even a single day, was recorded. The trajectory was described using a Sankey diagram. Results A total of 5,053 patients in the REIN registry and the SNDS database underwent peritoneal dialysis at some point. The Sankey diagram showed the great diversity and complexity of care pathways. Only 1,652 (33%) of patients underwent peritoneal dialysis only. A total of 1,807 (36%) patients changed kidney replacement therapy 2 times or more. There was high permeability between peritoneal dialysis and hemodialysis: 1,358 (27%) patients transferred from hemodialysis to peritoneal dialysis and 2,018 (40%) transferred from peritoneal dialysis to hemodialysis. A total of 251 (5%) patients underwent hybrid dialysis. A total of 498 (10%) patients experienced an unstable period of mixed dialysis and managed to return to peritoneal dialysis for a significant time (median of 339 days). The causes of transfers were not available. Conclusion Our results describe a more precise view of the trajectories of peritoneal dialysis patients compared to data from conventional registries. Peritoneal dialysis is a component of a multimodal pathway, as two thirds are likely to receive another kidney replacement therapies. Ongoing information about other kidney replacement therapies regimens seems necessary for peritoneal dialysis patients. The organization of each dialysis center must integrate and facilitate these transfers.